Utilization and transformation of Chrysotila dentata-derived dissolved organic matter by phycosphere bacteria Marinobacter hydrocarbonoclasticus and Bacillus firmus - Wang, Xueru; Fan, Chenjuan; Sun, Jun (PeerJ, 2024)
The dissolved organic matter (DOM) released from the cocoolithophores (Chrysotila dentata) was studied in laboratory experiments after co-culturing C. dentata with bacteria. Marinobacter hydrocarbonoclasticus (CA6)-γ-Proteobacteria and Bacillus firmus (CF2) were used to investigate the utilization and processing of the DOM derived from C. dentata, utilizing fluorescence excitation-emission matrix (EEM) combined with parallel factor analysis (EEM-PARAFAC), while measuring algal abundance and photosynthetic parameters. The experimental groups consisted of axenic C. dentata groups, filter cultured with bacteria (CA6 or CF2) groups, C. dentata co-cultured with bacteria (CA6 or CF2) groups and axenic bacteria (CA6 or CF2) groups. We then evaluated the processing of DOM by determining four fluorescence indices. The number of C. dentata cells and the photosynthetic capacity of microalgae were enhanced by CA6 and CF2. The main known fluorophores, including humic-like components and protein-like components, were present in all sample. The protein-like component of algal-bacterial co-cultures was effectively utilized by CA6 and CF2. The humic-like components increased at the end of the culture time for all cultures. Meanwhile, the average fluorescence intensity of protein-like in CA6 co-culture with algae was lower than that in CF2 co-culture with algae over time. On the other hand, the average fluorescence intensity of humic-like in CA6 was higher than CF2. However, the total change in fluorescence in humic-like and protein-like of axenic CF2 cultures was lower than that of CA6. Hence, the ability of CA6 to transform microalgal-derived DOM was superior to that of CF2, and CF2’s ability to consume bacterial-derived DOM was superior to that of CA6.
Keywords: Chrysotila dentata-derived DOM; Marinobacter hydrocarbonoclasticus; Bacillus firmus; EEM-PARAFAC; Fluorophores; Spectroscopic indices